Secret soldiers : how the U.S. twenty-third special troops fooled the Nazis - Janeczko, Paul B. (2019)
Paul B. Janeczko focuses his lens on World War II and the operations carried out by the Twenty-Third Headquarters Special Troops, aka the Ghost Army. This remarkable unit included actors, camouflage experts, sound engineers, painters, and set designers who used their skills to secretly and systematically replace fighting units -- fooling the Nazi army into believing what their eyes and ears told them, even though the sights and sounds of tanks and war machines and troops were entirely fabricated. Follow the Twenty-Third into Europe as they play a dangerous game of enticing the German army into making battlefield mistakes by using sonic deceptions, inflatable tanks, pyrotechnics, and camouflage in more than twenty operations. From the Normandy invasion to the crossing of the Rhine River, the men of the Ghost Army -- several of whom went on to become famous artists and designers after the war -- played an improbable role in the Allied victory."-- Jacket flap.
Ages 15+